2019
DOI: 10.1126/sciadv.aav4275
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-type systemic breast carcinoma cells with a restricted mesenchymal transition are a major source of metastasis

Abstract: Carcinoma cells undergo epithelial-mesenchymal transition (EMT); however, contributions of EMT heterogeneity to disease progression remain a matter of debate. Here, we addressed the EMT status of ex vivo cultured circulating and disseminated tumor cells (CTCs/DTCs) in a syngeneic mouse model of metastatic breast cancer (MBC). Epithelial-type CTCs with a restricted mesenchymal transition had the strongest lung metastases formation ability, whereas mesenchymal-type CTCs showed limited metastatic ability. EpCAM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
146
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 40 publications
(99 reference statements)
10
146
1
Order By: Relevance
“…Heterogeneity in epithelial and mesenchymal markers among breast cancer CTCs was reported in many studies [58,[60][61][62][63][64][65]. Moreover, it was reported, that the distribution of these markers in CTCs may be changing during disease progression and treatment [65].…”
Section: Emt Status In Ctcs and Its Prognostic Valuementioning
confidence: 96%
See 2 more Smart Citations
“…Heterogeneity in epithelial and mesenchymal markers among breast cancer CTCs was reported in many studies [58,[60][61][62][63][64][65]. Moreover, it was reported, that the distribution of these markers in CTCs may be changing during disease progression and treatment [65].…”
Section: Emt Status In Ctcs and Its Prognostic Valuementioning
confidence: 96%
“…Despite many studies, it is unclear which of those two distinct phenotypes may be prognostic for treatment response, PFS and OS. Some research show that mesenchymal phenotype is associated with poor outcome and shorter PFS [58,[65][66][67], but other studies suggest that prognostic value is rather associated with the epithelial phenotype [40,62]. Interestingly, the presence of mesenchymal CTCs was described a predictive factor, regardless of breast cancer subtype [58].…”
Section: Emt Status In Ctcs and Its Prognostic Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Aneuploidy-induced cell state transitions may be a novel cause of the strong correlation between aneuploidy and death from cancer. Additionally, recent evidence has underscored the importance of phenotypic plasticity in the metastatic cascade and has suggested that an EMT is neither a necessary nor an irreversible step in cancer cell dissemination (Chen et al 2019;Padmanaban et al 2019;Zheng et al 2015;Fischer et al 2015;Liu et al 2019). Instead, cancer cells can lose certain epithelial characteristics to promote migration out of the primary tumor site and into circulation, but they can re-establish them (through a mesenchymal-epithelial transition) in order to colonize a distant location (Dongre and Weinberg 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With continuous improvement in 5 CTC detection methods, CTC clusters were identified. Evidence has shown that CTCs in the clusters exhibit epithelial/mesenchymal hybrid (partial EMT) phenotype which allows them to move collectively (8). Collective movement makes these cancer cells to be more apoptosis-resistant and more capable of avoiding immune surveillance and colonizing distant organs.…”
Section: Introductionmentioning
confidence: 99%